Cytogenetic Analysis of Amniotic Fluid Cells in 4206 Cases of High-Risk Pregnant Women - Huafeng LI; Yongli LI; Rui ZHAO; Yanli ZHANG (Tehran University of Medical Sciences, 2019)
Background: We aimed to assess the frequency and structure of chromosomal abnormalities as well as the distribution of the indications of prenatal diagnosis in 4206 cases of high-risk pregnant women. Methods: A retrospective analysis of cytogenetic studies of 4206 pregnant women with indications of amniocentesis, referred to Linyi Women and Children's Hospital, Shandong Province, Linyi, China in 2016-2017, was performed. Among those, 4191 amniotic fluid specimens were successfully extracted and cultured, and received karyotype diagnosis. Results: A total of 358 abnormal karyotypes were detected and the abnormal rate was 8.54%. Among them, autosomal aneuploidy was the most common pattern occupied 64.53% and the detection rate was 5.51%, of which 173 (48.32%) cases were 21-trisomy, which was the main type of abnormal karyotypes, followed by 18-trisomy (14.25%). There were 38 cases with sex chromosome aneuploidy, including 47, XXY, 47, XXX, 47, XYY, 69, XXX and 45, X0, accounting for 10.61% of the total chromosome abnormalities and the detection rate was 0.91%. Chromosome structural disorders occupied 10.61% (38/358) of the chromosome abnormalities, including Robertson translocation (16 cases), balance translocation (14 cases), inversion (3 cases), deletion (3 cases), and so on. Chromosome polymorphism was 10.61% too. Other uncommon abnormal karyotypes included mosaicism (11/358), marker chromosome (1.3%). Advanced age and serological screening for high risk were the major prenatal diagnostic indications for pregnant women with chromosomal abnormalities. Conclusion: The karyotype analysis of amniotic fluid cells in pregnant women with different amniocentisis indications can effectively prevent the birth of fetuses with chromosomal diseases and reduce the risk of fetal malformation.